Physics ContributionsDose volume uniformity index: a simple tool for treatment plan evaluation in brachytherapy - Prabhakar, Ramachandran (Journal of Contemporary Brachytherapy, 2010)
Purpose: In radiotherapy treatment planning, dose homogeneity inside the target volume plays a significant role in the final treatment outcome. Especially in brachytherapy where there is a steep dose gradient in the dose distribution inside the target volume, comparing the plans based on the dose homogeneity helps in assessing the high dose volume inside the final treatment plan. In brachytherapy, the dose inhomogeneity inside the target volume depends on many factors such as the type of sources, placement of these radioactive sources, distance between the applicators/implant tubes, dwell time of the source, etc. In this study, a simple index, the dose volume uniformity index (DVUI), has been proposed to study the dose homogeneity inside the target volume. This index gives the total dose volume inhomogeneity inside a given prescription isoline. Material and methods: To demonstrate the proposed DVUI in this study, a single plane implant (breast: 6 catheters), a double plane implant (breast: 9 catheters) and a tongue implant (5 catheters) were selected. The catheters were reconstructed from the CT image datasets in the Plato treatment planning system. The doses for the single, double and tongue implants were prescribed to the reference dose rate as per the Paris technique. DVUI was computed from the cumulative dose volume histogram. Results: For a volume receiving a uniform dose inside the prescription isoline, the DVUI is 1. Any value of DVUI > 1 shows the presence of a relatively high dose volume inside the prescription isoline. In addition to the concept of DVUI, a simple conformality index, the dose volume conformality index (DVCI), has also been proposed in this study based on the DVUI. Conclusion: The DVUI and the proposed DVCI in this study provide an easy way of comparing the rival plans in brachytherapy.